2020
DOI: 10.3390/agronomy10040550
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops Affect Performance of Organic Scarlotta Seedless Table Grapes Under Plastic Film Covering in Southern Italy

Abstract: In sustainable or organic vineyard systems, the introduction of cover crops could represent a powerful tool for farmers to influence, positively, the agro-ecosystem by promoting the whole soil-plant system equilibrium. Concerning table grape production, nitrogen fertilizers are medium-high; for environmental aspects, organic viticulturists are more interested in legume inter-row cover crops. Research on cover crop effects was carried out in 2015–2016, on organic table grapes (the Sugranineteen variety) in Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Compared to the conventional tillage, cover crops produced an average increase of organic C content of 136%. This value was considerably higher than that found by Tarricone et al [25], who measured a 33% increase after two years of cover cropping in a Mediterranean vineyard, although starting from a higher initial organic C content in the bare soil (17.3 g kg −1 , against 2.6 g kg −1 of our study). Moreover, the more prolonged duration of cover crops in our study (up to six years) was responsible for the higher organic C accumulation in soil, as also evidenced by Fourie [26].…”
Section: Soil Chemical and Microbiological Propertiescontrasting
confidence: 89%
See 1 more Smart Citation
“…Compared to the conventional tillage, cover crops produced an average increase of organic C content of 136%. This value was considerably higher than that found by Tarricone et al [25], who measured a 33% increase after two years of cover cropping in a Mediterranean vineyard, although starting from a higher initial organic C content in the bare soil (17.3 g kg −1 , against 2.6 g kg −1 of our study). Moreover, the more prolonged duration of cover crops in our study (up to six years) was responsible for the higher organic C accumulation in soil, as also evidenced by Fourie [26].…”
Section: Soil Chemical and Microbiological Propertiescontrasting
confidence: 89%
“…Cover crops slightly reduced the berry detachment force in 2012 and 2013, whereas any difference was observed between the two treatments in 2014 ( Figure 7). Influence of different cover crops on the berry detachment force was reported by Tarricone et al [25], however, they did not evaluate this parameter under conventional tillage, thus no comparison with our data can be done.…”
Section: Yield and Grape Qualitative Parametersmentioning
confidence: 53%
“…Grape ecosystem services provided by Mediterranean vineyards are particularly threatened, because soil functions are often impaired by yearly repeated intensive agricultural practices or weed and pest management. The authors demonstrated that the potential of soil management practices to enhance soil functioning, can be promoted by the presence of a cover crop, even temporarily, in the inter row [20,21]. Moreover, Almagro found that improved soil management in rainfed Mediterranean agroecosystems can be a powerful strategy to mitigate the current atmospheric CO 2 increase, through soil carbon sequestration and stabilization [22].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the practices adopted in the treatments with the cover crop or temporary intercropping considerably improved the N self-sufficiency of the system. Beneficial effects have been found in grapes [20,21]. Grape ecosystem services provided by Mediterranean vineyards are particularly threatened, because soil functions are often impaired by yearly repeated intensive agricultural practices or weed and pest management.…”
Section: Introductionmentioning
confidence: 99%
“…Cover crops, however are reported as the main input of N to the soil. Tarricone et al (2020) reported an average of 18% increase in soil total N using subterranean clover (Trifolium subterraneum L.) or vetch as undervine cover crop in a table grape vineyard in Italy. The reduction in soil N in 0-30 cm depth in our study can be related to low N input using a grass-based cover crop (Tarricone et al 2020), light texture of the soil with low physical protection capacity (Maestrini et al 2015), possibility of N leaching, and high spatial variability in soil total N concentration (Poeplau and Don 2015).…”
Section: Soil C and N Contentmentioning
confidence: 99%